Properties of Recycled Polyethylene Terephthalate (rPET)/Stearic Acid/Green Mussel Shell (GMS) Composite - Ariani, Desi Budi; Nisa, Khadijah Sayyidatun; Aryanti, Fitria Ika; Hanifati, Ghina Sabrina (Jurnal Rekayasa Kimia & Lingkungan, 2025)
The increasing accumulation of plastic waste, particularly polyethylene terephthalate (PET), presents significant environmental challenges. This study explores the incorporation of green mussel shell (GMS) as a bio-filler in recycled polyethylene terephthalate (rPET) composites to promote sustainability and circular economy practices. rPET/SA/GMS composites were fabricated using injection molding, with GMS compositions of 0%, 5%, 10%, and 15% and a fixed 1% stearic acid (SA) content as a coupling agent. The effects of GMS on thermal, mechanical, rheological, and morphology properties were analyzed using differential scanning calorimetry (DSC), universal testing machine (UTM), melt flow index (MFI) testing, and scanning electron microscopy (SEM). The results indicate that 10% GMS exhibited the highest melting temperature (249.5C) due to enhanced interfacial interactions, despite a decrease in crystallinity. However, tensile strength decreased significantly at 5% GMS (8.52 MPa) due to weak interfacial bonding, whereas 10% GMS (12.91 MPa) showed slight improvement due to better SA-assisted dispersion. Rheological analysis revealed the highest melt flow rate (162.87 g/10 min) at 5% GMS, but higher GMS concentrations reduced flowability due to increased CaCO content and filler agglomeration. Morphological analysis confirmed that GMS addition increased surface roughness, induced void formation, and disrupted stress transfer, weakening composite integrity. These findings highlight the potential of GMS as a functional bio-filler in rPET composites, emphasizing the need for optimized filler concentration and interfacial modifications to develop sustainable high-performance materials.